BUILDING CONSUMER LOYALTY IN TRADITIONAL MARKETS: THE ROLE OF PRICE, LOCATION, PRODUCT DIVERSITY, QUALITY, AND RELATIONSHIP MARKETING - Purnomo, Nanto; Imron Hamzah, Muhammad (Magister Manajemen Universitas Islam Malang, 2025)
AbstractTraditional markets remain vital to local economies and social interactions in Indonesia but face growing pressure from modern retail and e-commerce, which are reshaping consumer behavior. Previous studies on the marketing mix and consumer loyalty have yielded inconsistent findings, highlighting the need for a more comprehensive approach. This study examines the influence of the marketing mix—price, location, product diversity, and product quality—together with relationship marketing on consumer loyalty in traditional markets. Relationship marketing is emphasized as a relational strategy that strengthens trust, communication, and long-term commitment. A quantitative survey method was applied, with 230 respondents selected using Hair’s sampling formula, based on the criterion of at least two purchase experiences in Pon and Kliwon Traditional Markets, Lamongan. Data were analyzed using multiple regression with SmartPLS to test both partial and simultaneous relationships among variables. The results indicate that price, product diversity, product quality, and relationship marketing significantly affect consumer loyalty, whereas location does not. Price is the most dominant factor, followed by relationship marketing, product quality, and product diversity. The findings demonstrate that consumers are highly sensitive to price and relational interactions, while location plays a lesser role due to the social and emotional values embedded in traditional markets. This study contributes to the literature by integrating functional and relational perspectives of marketing, offering a novel framework for enhancing consumer loyalty in traditional market contexts. Practically, the results suggest that traders and market managers should prioritize competitive pricing, maintain product quality and variety, and cultivate strong consumer relationships through personalized communication and trust-building. These strategies are crucial to improving the competitiveness and sustainability of traditional markets in the face of modern retail and digital commerce expansion.